The current status of routine hand washing compliance of nurses in clinical departments at Lam Dong General Hospital, 2017 - Tác giả (Tạp chí Khoa học Nghiên cứu Sức khỏe và Phát triển, 2017)
Hospital acquired infections is a challenge for the health sector, hand washing is main method, which has been effectively proved, and an important factor in control of hospital acquired infections